FOOT AND MOUTH DISEASE IN THE REPUBLIC OF KAZAKHSTAN: HISTORY AND PREVENTION STRATEGY - Myrzakhmetova, B.; Kutumbetov , L.; Zhapparova , G.; Tlenchiyeva , T.; Tussipova, A.; Bissenbayeva , K. (Eurasian Journal of Applied Biotechnology, 2024)
The global foot-and-mouth disease epidemic remains an extremely tense situation, and due to the spread of the SAT-2 pathogen beyond the African continent, a serious biological threat has arisen, threatening large economic losses to the livestock industry of all countries of the Eurasian continent, including the Republic of Kazakhstan. The territory of exotic danger of this type of foot-and-mouth disease is Iraq, Jordan and Turkey. The latter is an area of active visitation by the population of many countries of the world, forming the risk of transfer of the pathogen beyond this country. This article discusses current epidemiological knowledge and achievements, as well as strategies for preventing the spread of foot-and-mouth disease. Correct application of these strategies can successfully control and maintain a favorable epizootic situation for the disease in different parts of the country.